Migration background and educational tracking: Is there a double disadvantage for second-generation immigrants? - Elke Lüdemann; Guido Schwerdt (Center for Economic Studies and ifo Institute (CESifo), 2010)
Research on immigrants' educational disadvantages largely focuses on differences in student achievement tests. Exploiting data from the German PIRLS extension, we find that second-generation immigrants face additional disadvantages with respect to grades and teacher recommendations for secondary school tracks that cannot be explained by differences in student achievement tests and general intelligence. Second-generation immigrations are disproportionately affected by prevailing social inequalities at the transition to secondary school tracks due to their generally less favorable socio-economic background. We additionally provide new evidence suggesting that these inequalities might be related to the failing economic assimilation of immigrants.
Keywords: I21; J15; I28; 330; immigration; educational inequalities; educational tracking; Germany; Migranten; Bildungschancen; Bildungsabschluss; Soziale Integration; Deutschland